COMPARATIVE STUDY OF OXIDATIVE STRESS AND ANTIOXIDANT VITAMINS STATUS IN ALCOHOLIC LIVER DISEASE - A CASE-CONTROL STUDY - Kumar, Ranjeet; Gurupadappa K.; Mishra, Prakash Chandra (Student’s Journal of Health Research Africa, 2024)
Background Oxidative stress in the case of ALD can be treated with antioxidants which improve the treatment outcome of liver cirrhosis. It is necessary to determine the levels of vitamins which act as antioxidants. Objectives This study aimed to compare the levels of antioxidant vitamins in patients with ALD and the control group. Materials and Methods There were 60 controls and 60 ALD patients reporting at the gastroenterology department who were categorized as mild, moderate, and severe ALD. The bilirubin and MDA for oxidative stress were determined which indicated severity. The vitamin C & E levels were determined and compared between the controls and the study groups. Results The study included 120 participants. ALD participants had significantly higher weight and BMI compared to controls (p < 0.001), and most were male. Alcohol consumption increased with ALD severity, from 976.45±57.45 ml/week in the mild group to 1876.55±45.1 ml/week in the severe group, versus 355.12±50.1 ml/week in controls (p = 0.002). Age differences were not significant. Bilirubin in the severe ALD group was 6.4±0.34 mg/dl and in the control group was 0.92±0.2 mg/dl. MDA in the severe ALD group was 14.13±0.56 mg/dl and in the control group was 6.8±0.34 mg/dl. Vitamin C in the severe ALD group was 0.19±0.31 mg/dl and in the control group was 0.71±0.23 mg/dl. Vitamin E in the severe ALD group was 0.32±0.37 mg/dl and in the control group was 0.85±0.43 mg/dl. The difference in each case was statistically significant. Conclusion The severity of alcoholic liver disease increases with oxidative stress and with an increase in the bilirubin level. Also, in the case of severe liver disease, there is a significant decrease in vitamin C & E levels. Recommendation Vitamin C & E antioxidant therapy should be included in treating ALD.